Mentorship training program and mentors' competence in mercy community hospital, Iligan City - Dumlao, Cleroul Marietta F. (2000)
This study looked into the effectiveness of the mentorship training program on nurses who served as mentors at the Mercy Community Hospital in Iligan City. The main focus of the study was to see the contribution of this program in enhancing their mentor competence.Using a non-probability one group pretest-posttest research design, it targetted a total sample of the hospital. However, with the opportunity to work in foreign countries, what remained of the targetted sample numbered only 24 nurses. These became the actual study sample and they complied with the criterion that they should have a working experience of at least four years or more in the said institution. The study utilized a 41-item questionnaired textualizing beliefs and practices of mentorship in the identified situation. The items in the questionnaire were derived from culled literature review and from the actualities personnaly experienced by the investigator. In one way, the instrument is an original work contribution of this author which had undergone several pretests.Mentor factors such as age, sex, civil status, educational attainment, length of work experience and willingness to teach were studied in relation to their competence as mentors. Pretest was given to ascertain the level of competence of these nurses. Then the Mentorship Training Program was given and after a lapse of three days, the participants were given the posttest. Data were analyzed qualitatively with quantitative support using the arithmetical analysis of frequency-score relationship tandem. This type of analysis was recoursed to because the data were skewed towards a certain age-length of work experience group and would not follow a normal distribution scheme. The unpreventable exodus of the initial number of subjects made the actual and final sample quite small, thus limiting the correlation analysis with the simple arithmetical frequency-score relationship tandem.The paired t-test, preset at 95level of confidence was used to analyze the difference between the pre and post test scores with the Mentorship Training Program being the intervention or main variable. With this statistical analysis, the Mentorship Training Program made a significant effect on enhancing the nurses' competence as mentors. This was evident at the alpha value of 5.9056, placing a 95level of confidence.The effectiveness of the mentorship training program was borne out in this study. It is then recommended that such training program could be utilized to enhance mentorship competence of nurse who opt to teach. A continuation in research along this line will benefit many other nurses in standardizing this program. Nurses in the academe will find this training program also helpful in enhancing mentorship capabilities of nurses in teaching institutions.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Mentoring in nursing; Mentorship training